Single-belt vs. split-belt treadmill symmetry training: is there a perfect choice for gait rehabilitation post-stroke? - Yang, Chen; Veit, Nicole; McKenzie, Kelly; Aalla, Shreya; Embry, Kyle; Kishta, Ameen; Roth, Elliot; Jayaraman, Arun (Frontiers in Physiology, 2024)
Post-stroke gait asymmetry leads to inefficient gait and a higher fall risk, often causing limited home and community ambulation. Two types of treadmills are typically used for training focused on symmetry: split-belt and single belt treadmills, but there is no consensus on which treadmill is superior to train improve gait symmetry in individuals with stroke. To comprehensively determine which intervention is superior, we must considered multiple spatial and temporal gait parameters (step length, stride time, swing time, and stance time) and their symmetries. multiple components of human gait including not only symmetry, but also spatial and temporal gait parameters. We aimed to compare the effects of single session split-belt and single belt treadmill training on spatiotemporal gait parameters and their corresponding symmetries. Ten individuals with stroke underwent a single session of split-belt treadmill training and single belt treadmill training on separate days. The changes in step length, stride time, swing time, stance time and their respective symmetries were compared to investigate which training improves both spatiotemporal gait parameters and symmetries immediately after the intervention and after 5 minutes of rest. Both types of treadmill training immediately increased gait velocity (0.08 m/s faster) and shorter step length (4.15 cm longer). However, split-belt treadmill training was more effective at improving step length symmetry (improved by 27.3%) without sacrificing gait velocity or step length. However, this step length symmetry effect diminished after a 5-minute rest period. Split-belt treadmill training may have some advantages over single belt treadmill training, when targeting step length symmetry. Future research should focus on comparing the long-term effects of these two types of training and examining the duration of the observed effects to provide clinically applicable information.